PENANAMAN 1000 MANGROVE DI MANGROVE CENTER DESA BENGKAK KECAMATAN WONGSOREJO KABUPATEN BANYUWANGI - Reny Eka Evi Susanti (Fakultas Teknik, Universitas Bangka Belitung, 2023)
Swelling Mangrove Center is the name of a tourist spot in the village of Bengkak, Wongsorejo sub-district, Banyuwangi district, to be precise on Jalan Situbondo, Possumur Hamlet, with a land area of ​​around 4 hectares. The Swelling Mangrove Center is a combination of beach and mangrove tourism which is managed by a local community group called Pokmawas Tirta Wangi which is chaired by Mr. Sanijo. Based on the results of interviews with him, many of the Mangrove plants in the Mangrove Center have died and have not been cared for, apart from that there are still many vacant lands that have not been planted with mangroves. This is due to the low level of public awareness of the sustainability of mangrove forests. Based on the problems above, it is necessary to (1) socialize the importance of mangrove forests, the benefits of each part of the mangrove, and the procedure for planting mangrove seedlings, and (2) planting 1000 mangroves by inviting local communities and students in the village of Bengkak. After the community service activities were carried out, the community and students understood the importance of mangrove forests and knew the benefits of each part of the mangrove, starting from the seeds to the leaves, as well as the vacant land in the mangrove center, most of which had been planted with mangrove tree seedlings